2021
DOI: 10.1001/jamanetworkopen.2021.18253
|View full text |Cite|
|
Sign up to set email alerts
|

In Vitro Analysis ofN-Nitrosodimethylamine (NDMA) Formation From Ranitidine Under Simulated Gastrointestinal Conditions

Abstract: IMPORTANCE A publication reported that N-nitrosodimethylamine (NDMA), a probable human carcinogen, was formed when ranitidine and nitrite were added to simulated gastric fluid. However, the nitrite concentrations used were greater than the range detected in acidic gastric fluid in prior clinical studies.OBJECTIVE To characterize NDMA formation following the addition of ranitidine to simulated gastric fluid using combinations of fluid volume, pH levels, and nitrite concentrations, including physiologic levels. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 34 publications
2
24
0
Order By: Relevance
“…The study found no evidence of increased NDMA content in participants’ urine or blood ( Figure 2 ) who were administered ranitidine ( 12 ). Additional in vitro investigations with simulated gastric fluid supported that ranitidine would not produce NDMA under physiologic conditions ( 13 ). With this information, FDA may consider allowing ranitidine products back on the market if they are manufactured to be stable with low, acceptable amounts of NDMA that do not increase over time.…”
Section: Emergent Regulatory and Public Health Questionsmentioning
confidence: 99%
“…The study found no evidence of increased NDMA content in participants’ urine or blood ( Figure 2 ) who were administered ranitidine ( 12 ). Additional in vitro investigations with simulated gastric fluid supported that ranitidine would not produce NDMA under physiologic conditions ( 13 ). With this information, FDA may consider allowing ranitidine products back on the market if they are manufactured to be stable with low, acceptable amounts of NDMA that do not increase over time.…”
Section: Emergent Regulatory and Public Health Questionsmentioning
confidence: 99%
“…To the Editor A recent Editorial accompanying our published clinical trial in JAMA and in vitro studies in JAMA Network Open provides comments on our work that found no evidence of ranitidine converting to N -nitrosodimethylamine (NDMA) in humans. The editorial suggests that chloramine in tap water could facilitate ranitidine conversion to NDMA in humans, citing a study that assessed NDMA in chloraminated tap water 24 hours after adding ranitidine.…”
mentioning
confidence: 99%
“…The Editorial also suggests that consumption of a large, acidic, nitrite-rich meal by an obese person with a 2-L stomach volume could substantially increase NDMA production. However, this scenario is unlikely, as large meals are known to markedly increase pH, which substantially decreases the reactive form of nitrite . For additional context, in comparison with a fasting gastric pH of 1.2, which favors NDMA formation, approximately 70% of foods have a pH of 5 to 7, and 2% have a pH less than 3.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the Original Investigation “In Vitro Analysis of N -Nitrosodimethylamine (NDMA) Formation From Ranitidine Under Simulated Gastrointestinal Conditions,” 1 published June 28, 2021, there were errors in the captions for Figures 2, 3, and 4 and eFigure 3. The level of simulated gastric fluid in Figure 2 should have read 150 mg.…”
mentioning
confidence: 99%